2009
DOI: 10.1002/gps.2232
|View full text |Cite
|
Sign up to set email alerts
|

Use of physical restraints and antipsychotic medications in nursing homes: a cross‐national study

Abstract: SUMMARY Objectives This study compares inter- and intra-country differences in the prevalence of physical restraints and antipsychotic medications in nursing homes, and examines aggregated resident conditions and organizational characteristics correlated with these treatments. Methods Population-based, cross-sectional data were collected using a standardized Resident Assessment Instrument (RAI) from 14,504 long-term care facilities providing nursing home level services in five countries participating in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 39 publications
10
138
2
2
Order By: Relevance
“…Notably, the overall rate seems to have changed little in the last twenty years. Our national rate is similar or lower than rates reported in larger international studies in care homes in the US, Canada, Sweden, Finland, Switzerland and Australia and confirms that antipsychotic prescribing in care homes is not a parochial problem for the UK healthcare system but a challenge for all developed populations (Kamble et al, 2008;Lövheim et al, 2008;Rochon et al, 2007;Snowdon et al, 2005;Feng et al, 2009). Community prescribing is less well described and gender, regional and socio-economic differences have not been examined before.…”
Section: Discussionsupporting
confidence: 85%
“…Notably, the overall rate seems to have changed little in the last twenty years. Our national rate is similar or lower than rates reported in larger international studies in care homes in the US, Canada, Sweden, Finland, Switzerland and Australia and confirms that antipsychotic prescribing in care homes is not a parochial problem for the UK healthcare system but a challenge for all developed populations (Kamble et al, 2008;Lövheim et al, 2008;Rochon et al, 2007;Snowdon et al, 2005;Feng et al, 2009). Community prescribing is less well described and gender, regional and socio-economic differences have not been examined before.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to the report of Hamers et al [23], patients with a history of stroke and a diagnosis related to cognitive impairment comprised a large percentage of the restrained patients in our study. Age was often reported to be one of the predictors of physical restraint usage in studies [33]. Locally, Kwok et al (2006) observed that around 79% of older adults in his sample were restrained at one time or another during their hospital stay [34].…”
Section: Discussionmentioning
confidence: 95%
“…A multitude of physiological changes such as catecholamine rush, breakdown of muscle cells, pulmonary embolism, thrombophlebitis and psychological effects such as nightmares, intrusive thoughts, and avoidance responses have also been observed to result from restraint use [11]. Further, potential negative outcomes include increased incidence of falls, contractures, nosocomial infection, pressure ulcers, psychiatric morbidity, mental health problems, aggressive behavior, and mortality [12].…”
Section: Adverse Effects Of Restraint Usementioning
confidence: 99%
“…Rates of use in older people in European residential care facilities have been reported to be between 6 and 40%, with the higher rates thought to be due to the abundance of studies focusing on residents with dementia [4,9,[16][17][18]. US rates appear to have fallen over the years, with reports of prevalence of around 5% in acute settings and 9-30% in residential care settings [14,16,19].…”
Section: Prevalencementioning
confidence: 88%